Physical ergonomics: current requirements for the fashion designer (ModaPalavra e-periódico, 2016)
Apparel industries represent an important sector of the economy in Brazil. In 2012, the country was classified as the fourth largest trader of clothes and accessories manufacture in the world. Modeling, one of the activities that is part of the productive process of manufacture. In this study, we analyzed the activity carried out by a modeling bureau with the aim of identifying the physical requirements associated with the activity, as a way of generating a diagnosis and proposing improvement measures. To reach such a goal, the study was divided into a theoretical stage and an applied stage. The former sought to build a theoretical basis about the topic. The latter consisted of a case study conducted in a modeling bureau located in the city of Gaspar, Santa Catarina state. The study design involved observations, site visits, interviews and the application of the Nordic Questionnaire.
Keywords: ergonomics; designer; clothes making sector